Platform, descortinando em camadas as fronteiras do projeto de escrita de Guimarães Rosa em “O burrinho pedrês” - Silva, Arlete Borba da (2017)
The present research envisions a study of the short story “O burrinho pedrês” (“The Little Dust-brown Donkey”) by Guimarães Rosa, based on the author’s writing project, the so-called Platform project. The research unfolds through the analysis of the letters Guimarães sent to his translators, as well as interviews and statements given by the author. His Project enabled us to observe/perceive a line of thought that guides and directs translators into producing freer translations (CARVALHAL, 1993), whose essential aspects should meet those experienced by the writer in his creation process. Such notions can be verified in the narrative “The Little Dust-brown Donkey”, the most celebrated short story in the author’s debut book, as well as in his work in prose, configuring his inaugural quality within the national panorama that corresponds to the third generation of Modernism in Brazil (CANDIDO, 1989). Among other aspects, we highlight some characteristics in this short story that evoke folk tales (COELHO, 1987; PROPP, 1984); the fantastic literature (TODOROV, 2008); and the craft-like nature of narrative (BENJAMIN, 2012). In order to confirm the work’s experimental and hybrid quality, this study focuses on macro-micro relationships at both the structural and thematic levels between the main narrative and the mini narratives. All the factors raised have contributed to the visualization of an analogical framework, created by the comparison between the lives of men and animals, and have promoted a possible interpretation of the work in question